Psycholinguistic Analysis of Civil Servants’ Professional Activity Motivation with the Help of Sentence Completion Test - Malimon, Liudmyla; Hlova, Iryna (East European Journal of Psycholinguistics, 2015)
The article outlines a study of local executive body employee professional motivation. Sentence completion projective test along with content analysis were used as  method of research.  It was grounded the suitability of the methodology choice, its advantages in comparison with the survey methods of discovering of conscious and unconscious motives of professional activity in the system of governmental services. Content analysis of the sentences  completed by the respondents established personal significance and rating in the general structure of motivation of civil workers’ motivation set. Eleven groups of motives were identified. They included i) motives that concern socio-psychological peculiarities of an employee; ii) motives that are connected with duties and character of professional activity; iii) motives of stimulation and encouragement; iv) motives of interpersonal interaction; v) motives of interest in activity; vi) self-actualization; vii) constraint/influence of situation; viii) social usefulness; ix) life support; x) status and prestige; xi) career growth. It was identified that motives concerning employee’s socio-psychological features and those related to his duties and character of activity were more significant. However, motives of life support, status and prestige, and career growth were of less significance. ReferencesAnastazi, A. (2001). Differentsialnaya psihologiya. Individualnyie i gruppovyie razlichiyav povedenii. Moscow: Eksmo-Press.Bodalev, A., Stolin, V. ( 2002). Obschaya psihodiagnostika. S.-Petersburg: Rech.Burlachuk, L. (2006). Psihodiagnostika [Psychodiagnostics]. S.-Petersburg: Piter.Burlov, A. (2001). Metod neokonchennyih predlozheniy v sotsiologii [Method ofIncompleted Sentences in Social Studies]. Ph.D. thesis. Moscow: Institute of Social Studies.Hlova, I., Malimon, L. (2013). Psihologichniy analiz znachuschosti ta zadovolenostimotiviv profesiynoyi diyalnosti derzhavnyh sluzhbovtsiv mistsevih organiv vikonavchoyi vlady[Psychological analysis ]. Aktualni Problemy Psiholohii, 1, 37.Gurevich, K. (1998). Problemyi Differentsialnoy Psihologii [Issues of DifferentialPsychology]. Voronezh: MODEK.Leontyev, A. (2005). Osnovy Psiholingvistiki [Foundations of Psycholinguistics].Moscow: Smysl.Petrenko, V. (2005). Osnovy Psihosemantiki [Foundations of Psychosemantics]. S.-Petersburg: Piter.